Shape And Long Pipe Spiral Effect For The Temperature And Efficiency In Mini Boiler - Ismail Thamrin JMSE (Universitas Sriwijaya, 2016)
The researchers conducted a study on the modification of the pipe in the boiler mini spiral pipe shape with a length of 196.8 cm pipe. By purpose to increase efficiency and temperature that would be generated by a mini boiler and also to determine the shape and length of pipe that is better for use in mini boiler. Results of the testing showed that the temperature rise had passed through the pipe superheater, on the model of spiral pipe an increase in temperature of 10,92 ° C with a steam temperature of 277,62 ° C, while the temperature of incoming steam coming out of the pipe superheater at 288.54 ° C. Researchers previously known to occur at temperatures of 16,6 ° C rise in temperature of incoming steam superheater piping temperature of 267,4 ° C and 284 ° C steam out. Testing for heating water in the boiler mini was conducted for 90 minutes. Spiral pipe temperature value is better than the previous penilitian pipe and the efficiency in the can on mini boiler which uses the spiral pipe is equal to 14,957%, while in the previous study only 5,63%.